Implementasi Komunikasi Dakwah Muhammadiyah dalam Meningkatkan Kesadaran Agama - Indra Maulana; Milana Abdillah Subarkah (Jurnal Kajian dan Penelitian Umum, 2024)
Muhammadiyah employs various dakwah (Islamic propagation) methods such as sermons, religious gatherings, formal education, social and health activities, as well as cadre formation and training. The communication media utilized include print, electronic, and digital media. Case studies demonstrate Muhammadiyah's success in enhancing religious awareness through educational programs and community empowerment, despite challenges such as local cultural resistance and limitations in technology adaptation. The strengths of Muhammadiyah's dakwah strategy lie in its inclusivity and high adaptability to modern technology, while its weaknesses include technological limitations among members and local cultural resistance. Muhammadiyah's dakwah has proven effective in increasing religious knowledge and transforming societal attitudes and behaviors to be more Islamic. Supporting factors for this effectiveness include the active involvement of the younger generation and the infrastructural support from Muhammadiyah's educational and health institutions. However, digital divides and local cultural resistance require specific strategies to be addressed. Muhammadiyah has successfully leveraged modern media for more effective dakwah compared to traditional methods, which were more emphasized in previous studies. The challenges faced by Muhammadiyah receive more in-depth attention in this study, highlighting the need for more adaptive and inclusive dakwah strategies. This study underscores the importance of adaptation and innovation in dakwah and the necessity for inclusive strategies to overcome existing challenges to achieve a more significant impact in enhancing religious awareness in society.